Analisis Pengaruh Desentralisasi Fiskal dan Belanja Modal Daerah terhadap Pertumbuhan Ekonomi: Studi Kasus pada Kabupaten Sampang Tahun 2013-2022 - Aditya, Johan Rizky; Sudrajat, Ganjar Asdi; Pringgodani, Mardito Galih (Direktorat Sistem Perbendaharaan, 2024)
Fiscal decentralization, which grants authority over the management of Local Revenue (PAD), Transfers to Regions (TKD), and Regional Capital Expenditure, is expected to enhance regional economic growth. Despite possessing such authority and potential, Sampang Regency remains the area with the highest poverty rate and the lowest Human Development Index (HDI) in East Java. The purpose of this research is to analyze the effects of Local Revenue (PAD), Transfer to Regions (TKD), and regional capital expenditure on the economic growth of Sampang Regency. A mixed-methods approach was employed, combining quantitative analysis through multiple regression, as well as qualitative methods such as observations and discussions with the local government of Sampang Regency. The findings indicate that PAD and TKD positively influence economic growth in Sampang Regency, whereas regional capital expenditure negatively impacts the economic growth of Sampang Regency.